Operating Room and Flight Deck: What Do These Places Have in Common? - Maneechaeye, Pattarachat; Maneechaeye, Watcharaphat; Potipiroon, Wisanupong (Siriraj Medical Journal, 2021)
This review article grounds itself into the advent of aviation safety concepts that share some aspects into healthcare industry, practically and theoretically. These concepts are originally invented for aviation-related operation to ensure safety in flight but there are some aspects that can be related to healthcare context especially in surgery. Because aviation and healthcare are high reliability industries and neither patients nor passenger safety are compromised, safety concepts from aviation may prove useful for healthcare. The objective of this review was to scrutinize the concepts of aviation safety that may be applicable to healthcare. Data collection was based upon a review of literatures. This review article contributes to a broader knowledge from both fields of work regarding operational safety. The review shows that there are several practical concepts including Crew Resource Management, checklists and readbacks, sterile cockpit, and human factors of fatigue and stress that healthcare professionals can adopt and adapt them into their daily operation. Moreover, theoretical concepts such as Swiss cheese model and Threat and Error Management can be applied into healthcare context. This review invokes scenarios of each concept from both industries. The results show that communication is the key to promote safer operation and those concepts can be adopted to promote better safety at work. Future studies should extend the concepts of this review into an experimental research to analyze the effect of concepts on actual healthcare settings or utilize qualitative study to investigate the application of concepts in healthcare environment.